Status QUO of Technical Education - Srinivas, Ch. V.; Rama Devi, V.; Ratnakar, A.; Madhumurthy, K. (Journal of Engineering Education Transformations, 2008)
Technical education, by and large, is so lucrative on one side while illusive on the other, potential on one side and passive on the other, crazy on one side and care-not on the other. Globalization has made everything open to everyone, which is a boon in many suffer the lack of quality.